Pengaruh Aktivitas Pemasaran Media Sosial Terhadap Continuance Intention, Participation Intention, Dan Purchase Intention Pada Instagram Brand Hmns Parfumery - Aryadinata, I Gusti Agung Putra Indra; Giri, Refi Rifaldi Windya (eProceedings of Management, 2024)
In the current digital era, social media significantly influences consumer purchase intentions. The perfumeindustry in Indonesia leverages social media as a primary marketing tool. This study focuses on the impact ofsocial media marketing activities (SMMAs) on consumer purchase intentions, specifically Continuance Intention,Participate Intention, and Purchase Intention. The theoretical foundation includes key concepts such as SMMAs,intention, social identification, perceived value, and satisfaction. The independent variable is SMMAs, while thedependent variables are Continuance Intention, Participate Intention, and Purchase Intention, with socialidentification, perceived value, and satisfaction as mediators. Data was collected through questionnairesdistributed via Google Forms, with a sample of 385 respondents who are HMNS brand consumers and Instagramusers. The study employs purposive sampling and Structural Equation Modeling (SEM) using SmartPLS 4. Resultsindicate that SMMAs significantly and positively influence social identification, perceived value, and satisfaction.Furthermore, social identification significantly affects perceived value and satisfaction, while perceived valuesignificantly impacts satisfaction. Satisfaction, in turn, positively influences Continuance Intention, ParticipateIntention, and Purchase Intention. This study concludes that SMMAs impact customer intentions and providesstrategic recommendations for HMNS, including responsive customer service, digital campaigns, quality content,interactive content, loyalty programs, and customer testimonials. Keywords-Social Media Marketing Activities (SMMAs), consumer intention, social identification, perceivedvalue, satisfaction.